The role of psychological support interventions in trauma patients on mental health outcomes: A systematic review and meta-analysis. Issue 2 (August 2019) - Pham, Christopher H.; Fang, Mike; Nager, Jacqueline; Matsushima, Kazuhide; Inaba, Kenji; Kuza, Catherine M.
Abstract : BACKGROUND: The recovery and rehabilitation of trauma survivors may be long and challenging. Patients may be prone to psychiatric disorders, cognitive impairments, and decreased quality of life. The objective of this review was to determine whether there is a role for psychological interventions in reducing the incidence and severity of psychiatric sequelae in trauma survivors. METHODS: MEDLINE, PubMed, SCOPUS, and Google Scholar were searched for published articles. We searched for articles published between 1990 and 2018 with adult subjects, and limited our search to articles published in English. Randomized controlled trials that evaluated various psychiatric interventions in trauma patients on the effects of psychiatric outcomes were included for analysis. The articles were independently reviewed for eligibility by two different reviewers. A meta-analysis was performed on nine studies with similar interventions, outcomes measured, and patient populations. RESULTS: Nine hundred thirty-four articles were identified [830 articles identified through database search, and 107 through article references]. Sixty-nine full-text articles were reviewed for eligibility. Of these, 33 were included for qualitative analysis. Thirteen studies evaluating the effect of cognitive behavioral therapy (CBT)-based interventions on the severity of posttraumatic stress disorder (PTSD), anxiety, and depression symptoms underwent meta-analysis. While CBT-treated patients experienced clinically significant decreases in symptom severity, there were no statistically significant differences between treatment and control groups at follow-up for PTSD, anxiety, and depression. CONCLUSION: Compared with usual care, CBT-based interventions may not be effective in decreasing or preventing PTSD, anxiety, or depression symptoms in trauma survivors. LEVEL OF EVIDENCE: Systematic Review, level III. Abstract : Supplemental digital content is available in the text.